Living with obesity — existential experiences - Venke Ueland; Bodil Furnes; Elin Dysvik; Kristine Rørtveit (International Journal of Qualitative Studies on Health & Well-Being, 2019)
Aims and objectives: The aim was to gain in-depth understanding about individuals’ existential experiences of living with obesity. Background: People living with obesity face great vulnerability and existential challenges. The different treatments offered do not seem to meet the individual needs of persons with obesity. A deeper understanding of existential experiences from an individual perspective is needed to individualize treatment. Design: An exploratory phenomenological–hermeneutical design was used to gain a greater understanding of the existential experiences involved in living with obesity. Methods: The participants represented a convenient sample. 18 qualitative interviews were conducted and subjected to phenomenological–hermeneutical analysis. Results: Four themes emerged: shaped by childhood; captured by food; depressed by the culture; and judged by oneself. Conclusions: The burden of being obese can be experienced as being objectified and alienated as a human being. We need to turn towards a life-world perspective, seeing each human being as a living body to overcome objectification and alienation, and then move them towards becoming subjects in their own lives, through giving space for self-love. Health care workers need to assist persons living with obesity to reduce objectification and alienation. It is important to develop intervention that has an individual, holistic approach.